Ontogeny of the digestive enzyme activity of the Amazonian pimelodid catfish Pseudoplatystoma punctifer (Castelnau, 1855) - Castro-Ruiz D. (2019)
The aim of the study was to evaluate the functional ontogeny of the digestive system of Pseudoplatystoma punctifer through the analysis of the activity of the main intestinal (alkaline phosphatase, aminopeptidase N, maltase and leucine-alanine peptidase), pancreatic (trypsin, chymotrypsin, total alkaline proteases, bile-salt activated lipase and amylase) and gastric (pepsin) enzymes. Larvae were raised in triplicate in a recirculation system from 4 to 27 days post fertilization (dpf) at an initial density of 90 larvae L −1 , 27.8 ± 0.7 °C and 0 L: 24D photoperiod. Larvae were fed from 4 to 17 dpf with Artemia nauplii and weaned onto an experimentally formulated feed (crude protein content ~ 45%; crude fat content ~ 10%; crude carbohydrate ~ 8%) within 3 days, then continued with the same diet until the end of the trial. P. punctifer showed an exponential growth pattern with two different growth rates: a slower one from hatching to 12 dpf followed by a faster one from 12 to 27 dpf. The specific and total activities of the pancreatic and intestinal enzymes were detected from hatching. The digestive system was functional at 12 dpf, indicating the transition from the larval to the juvenile stage (alkaline to acid digestion). Therefore individuals could be weaned from that day onwards. The variations observed in the enzymatic activity from 17 dpf reflected the adaptation of the enzymatic machinery to the new diet supplied. P. punctifer larvae showed a fast digestive system development with an enzymatic profile typical of a tropical and carnivorous species. © 2019 Elsevier B.V.